Faktor-faktor yang memengaruhi implementasi anggaran berbasis kinerja - Kuntadi, Cris; Velayati, Ema (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Performance-based budgeting systems are becoming increasingly popular in developed countries around the world. Previous or related research is very important in research or scientific article writing. Previous research or related research helps strengthen the theory and phenomenon of the relationship or effect between variables. This paper examines the factors that influence the implementation of performance budgeting, namely: organizational commitment, resources and incentives and sanctions, as well as literature research on national financial management. The purpose of writing this article is to establish the hypothesis of influence between variables for further research. The results of this literature review are: 1) Organizational commitment influences performance budget implementation; 2) Resources influence the implementation of performance budgets; 3) Rewards and penalties affect the implementation of the performance budget.